Вплив умісту гемоглобіну в крові на кардіореспіраторну систему жінок - Качинська, Тетяна; Монюк, Люда; Kachynska, Tetiana; Monuk, Lyudmila (Східноєвропейський національний університет імені Лесі Українки, 2016)
Вивчено вплив умісту гемоглобіну в крові на функціональний стан кардіореспіраторної системи жінок зрілого віку. Адаптаційні та резервні можливості серцево-судинної системи характеризувалися кращими по- казниками в осіб із В12-фолієводефіцитною анемією й нормальним умістом гемоглобіну, порівняно з жінками із залізодефіцитною анемією. The purpose of the work was to study the effect of different hemoglobin in the blood on the functional state of the cardio-respiratory system of adult women. The study was conducted on 30 women aged 28–32 years. All subjects were divided into three groups: I – control group, women (10 persons) with normal blood hemoglobin; II –female (10 persons) with iron deficiency anemia; III – female (10 persons) with B12-folic acid-deficiency anemia. Determination of the concentration of hemoglobin in the blood test was carried out photometrically tsianmetgemoglobinovim. Adaptable and reserve the possibility of cardiovascular system characterized by the best performance in people with vitamin B12-folic acid deficiency anemia and normal hemoglobin compared to women with iron deficiency anemia. Female in the control group and B12-folic acid deficiency anemia are characterized by a good level of functional state of the respiratory system, whereas subjects with IDA-average.
Influence of Hemoglobin in the Blood of Women on the Cardiorespiratory System.
Keywords: залізодефіцитна анемія; гемоглобін; В12-фолієводефіцитна анемія; iron deficiency anemia; hemoglobin; B12-folic acid-deficiency anemia